Hematogenous Macrophages: A New Therapeutic Target for Spinal Cord Injury - Ding, Yuanzhe; Zhang, Di; Wang, Sheng; Zhang, Xiaolei; Yang, Jingquan (Frontiers in Cell and Developmental Biology, 2021)
Spinal cord injury (SCI) is a devastating disease leading to loss of sensory and motor functions, whose pathological process includes mechanical primary injury and secondary injury. Macrophages play an important role in SCI pathology. According to its origin, it can be divided into resident microglia and peripheral monocyte-derived macrophages (hematogenous Mφ). And it can also be divided into M1-type macrophages and M2-type macrophages on the basis of its functional characteristics. Hematogenous macrophages may contribute to the SCI process through infiltrating, scar forming, phagocytizing debris, and inducing inflammatory response. Although some of the activities of hematogenous macrophages are shown to be beneficial, the role of hematogenous macrophages in SCI remains controversial. In this review, following a brief introduction of hematogenous macrophages, we mainly focus on the function and the controversial role of hematogenous macrophages in SCI, and we propose that hematogenous macrophages may be a new therapeutic target for SCI.